Evolving procurement organizations: A contingency model for structural alternatives - Lydia Bals; Jari Laine; Godfrey Mugurusi (University of Applied Sciences Mainz, 2015)
Procurement has to find further levers and advance its contribution to corporate goals continuously. This places pressure on its organization in order to facilitate its performance. Therefore, procurement organizations constantly have to evolve in order to match these demands. A conceptual model putting the structural elements in focus is derived from the analysis of two case companies, which extends the existing literature and opens new avenues for future research. The findings highlight the importance of taking a contingency perspective on procurement organization, understanding the internal and external contingency factors and having a more detailed look at the structural dimensions chosen, beyond the well-known characteristics of centralization, formalization, participation, specialization, standardization and size. From a theoretical perspective, it opens up insights that can be leveraged in future studies in the fields of hybrid procurement organizations, global sourcing organizations as well as international procurement offices (IPOs). From a practical standpoint, an assessment of external and internal contingencies and their relation to specific structural dimensions that can be chosen provides the opportunity to consciously match an organization to its operating environment and internal demands.
Keywords: 650; Procurement; Purchasing; Supply Management; Sourcing; Purchasing and Supply Organization (PSO); Contingency Theory; Structure